MODERN MEASURES OF ANTI-TB INFECTION CONTROL - 10.2500 0581-2019-21-2-298-304; Z.T. AVGONOV; S.S. SATTOROV (Avicenna Tajik State Medical University, 2019)
For effective implementation of modern TB eradication measures should be available to data on TB transmission factors and epidemiology based on it pathogenesis, from infection before the outcome of its current. Review article reveals the modern requirements and methods of organizing anti-TB infection control. The results of the publications, their interpretation and comparison with the situation in Tajikistan are presented. The importance of following infection control measures at home, including the isolation of bacterioexcretion persons, timely verification of mycobacterium TB infection, vaccination and chemoprophylaxis to improve the TB epidemiological situation. It is noted that the evidence-based principles of preventing nosocomial transmission of TB infection have reduced the number of hospitalizations and minimized the duration of patients' stay in TB hospitals, while increasing the cohorts of patients who are initially on outpatient chemotherapy. The review presented and the real level of anti-TB infection control in the Republic of Tajikistan, especially in the nidus of infection and among contact persons, indicates the urgent need to rethink approaches to preventing transmission of this disease.